The experience of surgical repair of aortopulmonary windows in newborns - Y. V. Pisklova; D. A. Kulikova; O. V. Buchnieva (Ukrainian Journal of Cardiovascular Surgery, 2018)
Aortopulmonary window (APW) is a rare congenital malformation characterized by anomalous communication between the aorta and the pulmonary artery with normal dissociation of the aortic and pulmonary valves.Aim. In our report we present our experience in diagnosis and treatment of APW. Material andMethods. Three clinical cases are presented. Children were taken to a clinic with severe hemodynamic disorders caused by congenital heart disease. As a result of urgent operations, ALW was closed with or without correction of concomitant heart defects.Results and Discussion. With further observation, the children’s condition was stabilized. For successful treatment of APW is very important timely diagnosis, that can be difficult due to the lack of specific symptoms.Conclusions. Echocardiography is a key method of diagnosis of such defects. Surgical treatment is the method of choice in this pathology.